Mild Cognitive Impairment and Receipt of Treatments for Acute Myocardial Infarction in Older Adults - Levine, Deborah A. (J Gen Intern Med, 2019)
BACKGROUND: Older adults with mild cognitive impairment (MCI) should receive evidence-based treatments when indicated. Providers and patients may overestimate the risk of dementia in patients with MCI leading to potential under-treatment. However, the association between pre-existing MCI and receipt of evidence-based treatments is uncertain. OBJECTIVE: To compare receipt of treatments for acute myocardial infarction (AMI) between older adults with pre-existing MCI and cognitively normal patients. DESIGN: Prospective study using data from the nationally representative Health and Retirement Study, Medicare, and American Hospital Association. PARTICIPANTS: Six hundred nine adults aged 65 or older hospitalized for AMI between 2000 and 2011 and followed through 2012 with pre-existing MCI (defined as modified Telephone Interview for Cognitive Status score of 7–11) and normal cognition (score of 12–27). MAIN MEASURES: Receipt of cardiac catheterization and coronary revascularization within 30 days and cardiac rehabilitation within 1 year of AMI hospitalization. KEY RESULTS: Among the survivors of AMI, 19.2% had pre-existing MCI (55.6% were women and 44.4% were male, with a mean [SD] age of 82.3 [7.5] years), and 80.8% had normal cognition (45.7% were women and 54.3% were male, with a mean age of 77.1 [7.1] years). Survivors of AMI with pre-existing MCI were significantly less likely than those with normal cognition to receive cardiac catheterization (50% vs 77%; P < 0.001), coronary revascularization (29% vs 63%; P < 0.001), and cardiac rehabilitation (9% vs 22%; P = 0.001) after AMI. After adjusting for patient and hospital factors, pre-existing MCI remained associated with lower use of cardiac catheterization (adjusted hazard ratio (aHR), 0.65; 95% CI, 0.48–0.89; P = 0.007) and coronary revascularization (aHR, 0.55; 95% CI, 0.37–0.81; P = .003), but not cardiac rehabilitation (aHR, 1.01; 95% CI, 0.49–2.07; P = 0.98). CONCLUSIONS: Pre-existing MCI is associated with lower use of cardiac catheterization and coronary revascularization but not cardiac rehabilitation after AMI. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05155-8) contains supplementary material, which is available to authorized users.